Digital skills and its potential : The digital transformation of Russia - Trofimova, Irina; Morgan, John W. (My University, 2020)
"65 percent of children entering primary school today will work in employment that does not yet exist; and by 2022 approximately 22 percent of employment in the global economy will be created by digital technologies. 73 percent of company managers say they have serious problems finding specialists qualified in such technologies, compared with 10 percent in 2010. This shows the speed of the changes to which digitalisation is fundamental."(author' abstract; BIBB-Doku)
Keywords: I 2.2.2 Osteuropa; G 1.2 Arbeitsmarkt; Digitalisierung; Transformation; Arbeitsmarkt; Digitalkompetenz; E-Learning; Russland